Adventure time explore the dungeon because I don't know! [PS3] - D3Publisher of America (Los Angeles, CA. D3Publisher of America, 2013)
Princess Bubblegum summons Finn and Jake to investigate a rash of thefts and kidnappings that are plaguing the Candy Kingdom. She suspects the cause lies within her Secret Royal Dungeon, where the nastiest monsters and criminals are locked up.
Blu-ray disc.
Title from disc label.
1-4 players.
ESRB content rating: E 10+, Everyone 10+ (cartoon violence, comic mischief).
System requirements: Playstation 3.
Container in English, French, and Spanish.
Keywords: Criminals -- Computer games; Prisons -- Computer games; Heroes -- Computer games; Fantasy -- Computer games; Video games; Sony video games; Criminals; Fantasy; Heroes; Prisons; Sony video games; Video games; Computer games